2017
DOI: 10.1021/acs.est.7b03196
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Multiple Environmental Factors on Organic Matter Chlorination in Podsol Soil

Abstract: Natural chlorination of organic matter is common in soils. The abundance of chlorinated organic compounds frequently exceeds chloride in surface soils, and the ability to chlorinate soil organic matter (SOM) appears widespread among microorganisms. Yet, the environmental control of chlorination is unclear. Laboratory incubations with Cl as a Cl tracer were performed to test how combinations of environmental factors, including levels of soil moisture, nitrate, chloride, and labile organic carbon, influenced chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…In this study, we cannot elucidate whether the observed chlorination was due to biotic or abiotic processes, but the presence of plants significantly enhanced soil organic matter chlorination. We hypothesize this was because root exudates of labile organic matter stimulated microbial activity in ways the promoted chlorination, in accordance with Svensson et al (2017).…”
Section: Org Levels In Plant Biomasssupporting
confidence: 68%
See 2 more Smart Citations
“…In this study, we cannot elucidate whether the observed chlorination was due to biotic or abiotic processes, but the presence of plants significantly enhanced soil organic matter chlorination. We hypothesize this was because root exudates of labile organic matter stimulated microbial activity in ways the promoted chlorination, in accordance with Svensson et al (2017).…”
Section: Org Levels In Plant Biomasssupporting
confidence: 68%
“…Despite the fact that the current study is laboratory based and the results cannot directly be extrapolated or upscaled to field conditions, it is clear that extensive natural chlorination and dechlorination of organic matter in soil and Cl turnover is likely linked to common ecosystem processes and that plants and plant/root-associated organisms can have a major influence on these processes. Indeed, different Cl accumulation rates have been linked to forest types and chlorination rates were recently associated with the microbial activity (Montelius et al 2015;Svensson et al 2017). The results indicate that Cl − is rapidly taken up by plants at higher concentrations than those needed for growth, though the reason for this additional uptake is unknown.…”
Section: Net Changes Of CL − and Cl Org In Bulk Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…Varying the nitrogen levels has yielded ambiguous results (Bastviken et al 2006, Rodhstedt 2000, and local variability seems large. A factorial study showed that total chlorination was hampered by addition of nitrate or by nitrate in combination with water but enhanced by addition of chloride as well as labile organic matter (glucose and maltose) (Svensson et al 2017). These estimates were based on studies of bulk soil excluding roots, which likely has underestimated the chlorination potential as it was later suggested that most of the chlorination takes place in the rhizosphere (Montelius et al 2019).…”
Section: Processes Driving Terrestrial CL Cyclingmentioning
confidence: 99%
“…The extensive natural chlorination processes in soil suggest that the Cl turnover likely is linked to common ecosystem processes. Indeed, chlorination rates were recently linked to microbial activity (Svensson et al 2017), but the fundamental reasons for the extensive soil Cl-cycling are still unclear. A recent review discusses the microbial metabolism of Cl org and the possible links between chlorinating and dechlorinating microbes (Atashgahi et al 2018).…”
Section: Introductionmentioning
confidence: 99%